Altered Mitochondrial Function in MASLD: Key Features and Promising Therapeutic Approaches - Tatjana Radosavljevic; Milica Brankovic; Janko Samardzic; Jasmina Djuretić; Dusan Vukicevic; Danijela Vucevic; Vladimir Jakovljevic (MDPI AG, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as nonalcoholic fatty liver disease (NAFLD), encompasses a range of liver conditions from steatosis to nonalcoholic steatohepatitis (NASH). Its prevalence, especially among patients with metabolic syndrome, highlights its growing global impact. The pathogenesis of MASLD involves metabolic dysregulation, inflammation, oxidative stress, genetic factors and, notably, mitochondrial dysfunction. Recent studies underscore the critical role of mitochondrial dysfunction in MASLD's progression. Therapeutically, enhancing mitochondrial function has gained interest, along with lifestyle changes and pharmacological interventions targeting mitochondrial processes. The FDA's approval of resmetirom for metabolic-associated steatohepatitis (MASH) with fibrosis marks a significant step. While resmetirom represents progress, further research is essential to understand MASLD-related mitochondrial dysfunction fully. Innovative strategies like gene editing and small-molecule modulators, alongside lifestyle interventions, can potentially improve MASLD treatment. Drug repurposing and new targets will advance MASLD therapy, addressing its increasing global burden. Therefore, this review aims to provide a better understanding of the role of mitochondrial dysfunction in MASLD and identify more effective preventive and treatment strategies.